ANALISIS STARTEGI PEMASARAN PADA MINAT BELI KONSUMEN TERHADAP PRODUK KOSMETIK IMPLORA PADA MASYARAKAT SUKARAME - Yustika Safira; Prajawantoro Prajawantoro (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
The purpose of this research is to find out the factors that are used for the sale of Implora products to attract the attention of consumers in Sukarame Bandar Lampung. And how to increase the position of Implora in Sukarame Bandar Lampung Cosmetics market. This research method uses SWOT analysis with a qualitative descriptive approach, with the results of the research are and the sale of Implora Cosmetics at Toko Nia Cosmetics also have a better chance of being compared to the threat factors of (0.17). Judging from the Cartesius SWOT diagram, it is known that Implora Cosmetics sales in Toko Nia Cosmetics are in II position Growth (growing) position